Effects of Calcium and Magnesium Application on Yield and Fruit Quality of Oranges in Thanh Hoa Province, Vietnam - Hien Huu Nguyen; Dung Cao Thi Thu; Nhung Thi Ho; Mai Thanh Thị Nguyen; Lam Ngoc Thai; Hien Thi Nguyen (Caraka Tani: Journal of Sustainable Agriculture, 2026)
Calcium (Ca) and magnesium (Mg) are essential secondary macronutrients that govern plant growth, fruit development, and physiological stability of citrus production. Specifically, these elements play a crucial role in mitigating fruit cracking and enhancing fruit quality. The objective of the study was to determine the optimal application rates of Ca and Mg to maximize yield and fruit quality of Xa Doai oranges in Thanh Hoa Province, Vietnam. The experiment was conducted from December 2024 to December 2025 on seven-year-old Xa Doai orange trees, using a randomized complete block design and 3 replications. Treatments consisted of 3 levels of Ca (2.0, 2.5, and 3.0 kg tree-¹) and Mg (0.5, 1.0, and 1.5 kg tree-¹). The results showed that the application of 3.0 kg CaSO₄.2H₂O and 1.5 kg MgSO₄.7H₂O were effective in improving soil pH (6.35) and resulted in high exchangeable Ca and Mg (1,012.60 and 188.33 mg kg-¹, respectively) and the lowest level of fruit cracking (10.82%). Conversely, the highest yield (50.84kg tree-¹), total soluble solids (TSS, 11.53%), and TSS/TA ratio (25.61) were obtained with the lower application rates of 2.0 kg CaSO₄.2H₂O mixed with 0.5 kg MgSO₄.7H₂O. Analysis results indicated that the exchangeable Ca in soil was negatively correlated with fruit weight (r = -0.77), fruit circumference (r = -0.70), fruit cracking (r = -0.90), TSS (r = -0.75), and TSS/TA ratio (r = -0.94), but positively correlated with peel thickness (r = 0.88). The results offer a viable basis for maximizing fertilization in the production of oranges.